The Influence of the School Literacy Movement on the Reading Comprehension Ability of Grade III Students - Fitriani, Sri Rahayu; Labudasari, Erna; Jannah, Widia Nur (EduHumaniora | Jurnal Pendidikan Dasar Kampus Cibiru, 2024)
This study aims to determine the effect of the school literacy movement on the reading comprehension ability of third grade students at SDN 2 Dukuhwidara. This type of research used a quantitative approach. The design was experimental method. The form of the research design was Pre-Experimental Designs (non-designs) with a variety of One-Group Pretest-Posttest Design. Data were collected from observation, pretest-posttest test in the form of essays and documentation studies. Data analysis techniques used prerequisite tests, namely tests for normality, homogeneity, N-gain and hypothesis testing, namely correlation tests, regression tests and tests of the coefficient of determination with the provisions that Ha was accepted and Ho was rejected. The results of the study showed that there was a positive and significant influence between the school literacy movement on the reading comprehension ability of third grade students at SDN 2 Dukuhwidara. As for the results of the hypothesis test, the correlation test was 0.0000.05 with a correlation level of 0.807 which was positive and the regression test obtained data that had a significance of 0.0000.05, in other words the hypothesis proposed was accepted, namely Ha was accepted and Ho was rejected. The magnitude of the influence of the school literacy movement on students' reading comprehension ability is 65.2% while the rest is influenced by other factors.